Precipitation modulates the net effect of solar radiation on litter decomposition and CO2 emission - a meta-analysis - Liu, YaLan; Li, Lei; Wang, ShiQi; Li, Xiangyi (Frontiers in Plant Science, 2023)
Introduction: Solar radiation plays a crucial role in the decomposition of litter and the cycling of nutrients from soil to the atmosphere. Although previous research has investigated the contribution of photodegradation to litter decomposition in semi-arid and arid ecosystems with limited precipitation, there is a gap in understanding the net impact of this process on a global scale, particularly in relation to different precipitation levels. Method: To address this gap, we conducted a comprehensive meta-analysis of 351 datapoints from 37 published studies to estimate the sole radiation effect and the interactive effects of precipitation on a global scale, and how they vary for different precipitation levels. We assess the importance of each factor which influence of the effect of radiation and identify the key drivers. Results: Our findings suggest that solar radiation largely regulates litter decomposition and that the direction and magnitude of its effects are potentially dependent on the precipitation regime. We found that the effect of radiation on litter decomposition has a linear relationship with precipitation levels, except when precipitation exceeds 800mm. The effect of radiation on lignin remaining for precipitation levels above 800mm lower than in levels below 200mm. Furthermore, radiation had a significant negative effect on MBC when precipitation exceeded 800mm, but had no significant effect when precipitation was below 200mm. Interestingly, we found that the effect of radiation on CO2 emissions varied from 13.97% when precipitation was below 200mm to -0.707% when precipitation was between 200-400mm. Conclusion: Initial litter trait especially lignin concentration determines litter decay rate in arid lands while climate factors appear to have a greater influence on litter decomposition in ecosystems that are not moisture-limited. Precipitation will shift the mechanism of lignin decomposition and the main effect of radiation will shift from "photopriming" to "microbial inhibition" under high precipitation levels. Our findings have important implications for understanding litter decomposition patterns on a global scale and our results showed that CO2 emissions from photodegradation processes will be lessened by precipitation, which is important in predicting CO2 emission and separating sources of CO2 under future increasing precipitation scenarios.